Analisis Kesesuaian Akuntansi Transaksi Gadai Emas Syariah Dengan PSAK dan Fatwa DSN MUI (Studi Kasus Kantor Pegadaian Unit Pelayanan Syariah Langsa Baro) - Rizka Safitri; Juliana Nasution (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
Pegadaian is an one of the choises for people to borrow funds is pawning gold due to the easiness of procedures and fast processing. The basic of mortgage in sharia is Fatwa no.25/DSN MUI/III/2022 regarding Rahn and Fatwa no.26/DSN MUI/III/2002 regarding gold pawning, and PSAK 107 about Ijarah, PSAK 59 abou Qard and PAPSI 2013. This study aims to determine the accounting treatment of gold pawn products at the sharia pawnshop, case study at the Langsa Baro Sharia Service Unit. The method used in this research is a qualitative. The result of this research is accounting measurement for gold pawn in sharia pawnshop has followes PSAK no.59, PSAK 107 and PAPSI 2013. However, in presenting the financial statements on gold pawning in sharia pawnshop, its not the same as PSAK no.100 and PSAK no.101.